A systematic review of Clinical Practice Guidelines for the development of the WHO's Package of Interventions for Rehabilitation: focus on schizophrenia - Serra, Riccardo; Etemadi, Yasaman; van Regteren Altena, Marieke; Barbui, Corrado; Tarsitani, Lorenzo (Frontiers in Public Health, 2023)
Background The identification of interventions for rehabilitation and related evidence is a crucial step in the development of World Health Organization's (WHO) Package of Interventions for Rehabilitation (PIR). Interventions for rehabilitation may be particularly relevant in schizophrenia, as this condition is associated with a high risk of disability, poor functioning, and lack of autonomy. Aiming to collect evidence for the WHO PIR, we conducted a systematic review of Clinical Practice Guidelines (CPG) on interventions for rehabilitation of schizophrenia. Methods Methods for the systematic identification and critical appraisal of CPG were developed by WHO Rehabilitation Programme and Cochrane Rehabilitation under the guidance of WHO's guideline review committee secretariat. The Appraisal of Guidelines for Research & Evaluation Instrument (AGREE II) was used to evaluate the methodological quality of identified CPG. Results After full text screening, nine CPG were identified, for a total of 130 recommendations. Three were excluded because their total AGREE-II scores were below cut-off. Six CPG were approved by the Technical Working Group and included for data extraction. Only one CPG with specific focus on rehabilitation of schizophrenia was retrieved. Other CPG were general, including some recommendations on rehabilitation. Some CPG gave no indications on the assessment of rehabilitation needs. Discrepancies were detectable, with different CPG emphasizing different domains. Most recommendations addressed “symptoms of schizophrenia,” while “community and social life” was targeted by few recommendations. International CPG were often conceptualized for high-income countries, and CPG accounting for their implementation in lower income contexts were scarce. Quality of evidence was high/moderate for 41.54% (n = 54) of the recommendations, and very low only in two cases (1.52%). N = 45 (34.62%) were based on experts' opinion. Conclusions The concepts of recovery and rehabilitation in schizophrenia are relatively new in medical sciences and somewhat ill-defined. An unbalanced distribution in the domains addressed by available CPG is therefore understandable. However, the need for more focus in some areas of rehabilitation is obvious. More clarity is also required regarding which interventions should be prioritized and which are more feasible for global implementation in the rehabilitation of schizophrenia.